Formaldehyde-inactivated whole-virus vaccine protects a murine model of enterovirus 71 encephalomyelitis against disease - Ong, K.C.; Devi, S.; Cardosa, M.J.; Wong, Kum Thong (American Society for Microbiology, 2010)
Enterovirus 71 (EV71) causes childhood hand, foot, and mouth disease and neurological complications, and no vaccines or therapeutic drugs are currently available. Formaldehyde-inactivated whole-virus vaccines derived from EV71 clinical isolates and a mouse-adapted virus (MAV) were tested in a mouse model of EV71 encephalomyelitis. After only two immunizations, given to mice at 1 and 7 days of age, the MAV vaccine protected mice at 14 days of age from disease. Tissues from immunized mice were negative for virus by viral culture, reverse transcriptase PCR, immunohistochemistry analysis, and in situ hybridization. Cross-neutralizing EV71 antibodies to strains with genotypes B3, B4, and C1 to C5 generated in immunized adult mice were able to passively protect 14-day-old mice from disease.